Comparative effectiveness of herb-partitioned moxibustion plus lifestyle modification treatment for patients with simple obesity: A study protocol for a randomized controlled trial. Issue 3 (22nd January 2021) - Wang, Li-Hua; Lv, Si-Ying; Liu, Yi-Ran; Chen, Xia; Wang, Jia-Jie; Huang, Wei; Zhou, Zhong-Yu
Abstract: Introduction: Obesity is a global public health issue, which results in many health complications. Moxibustion may serve as an alternative management for simple obesity, where pharmacological therapy is always difficult to be accepted by the majority of obese patients based on its safety. However, the effects of herb-partitioned moxibustion as obesity intervention have not been confirmed. This study is designed as a single-blinded, 3-dummy randomized controlled trial to evaluate the efficacy and safety of herb-partitioned moxibustion plus lifestyle modification treatment in patients with simple obesity. Methods and analysis: This study will be a randomized, controlled trial conducted from April, 2019 to April, 2021 that includes 108 participants who have simple obesity and meet the eligibility criteria. The participants will be randomly divided into 3 treatment groups: heat application group, medicated plaster group, or herb-partitioned moxibustion group. Each treatment will last 4 weeks. The primary outcomes will be the clinical effectiveness. The secondary outcome measures include participants' obesity-related indicators, the IWQOL-Lite scale, and the syndrome score of Traditional Chinese Medicine. Adverse events will be recorded during the intervention period. Ethics and dissemination: Ethical approval of this study was granted by the Ethics Committee of Hubei Provincial Hospital of Traditional Chinese Medicine on 15 November 2018 (Ethics Reference No: HBZY2018-C24-01). Written informed consents will be provided by all participants before they were enrolled in this study. Trial registration number: NCT04606680